SIMULASI JADWAL UJIAN NASIONAL MENGGUNAKAN ALGORITMA GENETIK - Hambali Hambali; Feri Hari Utami ((JurTI) Jurnal Teknologi Informasi, 2017)
Abstrack - Scheduling of national examination supervisors is done by crossing, the crossing is done by applying a genetic algorithm approach. Genetic algorithm is one way to solve a fairly large problem with a fairly good solution even though the problem requires a long execution time if done manually. Genetic algorithms are good enough to be used in scheduling supervisors in a junior secondary school. Based on the results of the discussion and testing it can be concluded as follows: National Examination Schedule Simulation Program Using Genetic Algorithms using PHP-Mysql can find out information systems and reports for each National Examination Monitoring Schedule, National Exam Schedule Simulation Using Genetic Algorithms Using PHP-MySql, can be used by Education and cultural services with evaluation data.   Keywords - Scheduling, PHP-Mysql, Genetic Algorithms